Nanti Kita Cerita Hari Ini : Jhon Fiske Signs and Marks As A Movie - Aidha Syafira Dharma (Universitas Pendidikan Indonesia, 2022)
All the emotions and pain and the mutual hiding of their feelings within a family can be felt in a film showing NKCTHI: One Day We’ll Talk About Today. A film based on a book by Marcella FP, this film with a family theme has a background story that usually carries a fairly complicated conflict. Besides being able to bring the emotions of laughter and tears, films with family themes also have the benefit of conveying messages in everyday social life. With the achievement of reaching more than 2 million viewers, enthusiasm and trending topic in the world of social media, as well as being discussed by many communities and society in general regarding the film, the researcher is interested in raising the topic of discussing the contents of the story of the NKCTHI film, especially to get answers about what the actual contents are. or the message conveyed in the storytelling in the NKCTHI film by using John Fiske's Semiotics analysis. The method used in this study uses qualitative methods with a semiotic analysis approach, which will be interpreted into John Fiske's three semiotic levels, namely the level of reality, then the level of representation, and the level of ideology. The existence of ideological differences in the three brothers proves that there are differences even from the same sphere. And in a family that looks harmonious and looks happy, it doesn't necessarily belong to a good family